2020
DOI: 10.3390/ijerph17197315
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Determinants of Children’s Inadequate Sleep Health. A Concept Mapping Study among Professionals

Abstract: An increasing number of children experience inadequate sleep, which negatively effects their health. To promote healthy sleep among children, it is essential to understand the underlying determinants. This online concept mapping study therefore explores potential determinants of children’s inadequate sleep as perceived by professionals with expertise in the sleep health of children aged 4–12 years. Participants (n = 27) were divided in three groups: (1) doctors (n = 9); (2) nurses (n = 11); (3) sleep experts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Other domains of the CFPQ were not included as these were less relevant to the purpose of this study. The items of the domains of the original questionnaire were adapted and translated into sleep practices, based on findings in the scientific literature (Adam et al, 2007; Belmon, Brasser, et al, 2020; Belmon, Busch, et al, 2020; Gruber et al, 2014). Parents answered the questions on a 5‐point Likert scale, ranging from (1) “never” to (5) “always”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other domains of the CFPQ were not included as these were less relevant to the purpose of this study. The items of the domains of the original questionnaire were adapted and translated into sleep practices, based on findings in the scientific literature (Adam et al, 2007; Belmon, Brasser, et al, 2020; Belmon, Busch, et al, 2020; Gruber et al, 2014). Parents answered the questions on a 5‐point Likert scale, ranging from (1) “never” to (5) “always”.…”
Section: Methodsmentioning
confidence: 99%
“…fear, affective state) and evening activities (e.g. playing stimulating games before sleeping) as important factors of children’s sleep health (Belmon, Brasser, et al, 2020; Belmon, Busch, et al, 2020). For social and community network factors, previous research indicated that parental pre‐sleep emotional support (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a systematic review to summarize the longitudinal evidence for factors related to children's sleep health (i.e., sleep duration, sleep quality, and sleep timing) ( 20 ). Next, two concept mapping studies were performed with different stakeholder groups (i.e., children aged 9-12 years, parents of children aged 4-12 years, and professionals) from various cultural backgrounds to explore the perceived determinants of children's inadequate sleep health ( 21 , 22 ). These mixed-method studies were supplemented with a cross-sectional study among a culturally diverse group of children and their parents in Amsterdam ( n = 382) to explore potential factors related to children's sleep (i.e., sleep duration, sleep quality, and sleep timing).…”
Section: Methodsmentioning
confidence: 99%